komparasi karya seni lukis MOOI Indie Antara Seniman Indonesia dan Seniman Dari Barat Periode 1930-an - Pandanwangi, Ariesa (Jurnal Budaya Nusantara, 2019)
The purpose of this study is to compare the 1930s indie mooi painting works between Indonesianartists and western artists. The samples of this study were paintings of Indonesian artists andWestern artists made in 1930s. Each work of these artistsis selected to represent his period. Hiswork is, therefore, analyzed using Feldman's theory. The results of this study show that manyartists' creative ideas are inspired by the scenery of Indonesia. These creative ideas lead to themesemerged which visualizing fields and mountains on their indie mooi paintings. The primarilyreason of visualizing the beautiful scenery on their paintings is that these paintings are intended tofavourEuropean communities living in Java. Another result of the study is that paintings at thattime still used traditional techniques and media, oil paint on canvas and the colours used aremostly bright.